2020
DOI: 10.1016/j.ijid.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia bacteremia: A single-center retrospective review and a systematic review of the literature

Abstract: Objectives: Nocardia bacteremia is a rare but severe disease associated with high mortality. This systematic review is the largest and most comprehensive review performed over the past 20 years. Methods: A single-center retrospective review of Nocardia bacteremia was performed using hospital microbiology records from January 1, 2010 to December 31, 2017. A systematic literature review was also performed to identify cases of Nocardia bacteremia described in the NCBI PubMed database in English between January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 109 publications
(24 reference statements)
1
47
0
Order By: Relevance
“…Nocardiosis most frequently presents with pulmonary disease, followed by disseminated disease, extra-pulmonary disease [such as in the central nervous system and primary skin and soft tissue disease (2)]. Nocardiosis is regarded as an opportunistic infection, with the majority of infections occurring in immunocompromised patients, including those with long-term corticosteroid exposure, malignancy, human immunodeficiency virus (HIV) infection, and history of transplantation (3)(4)(5)(6)(7), associated with high mortality of 34.5-40% (3,4). Xu L. et al (8) reviewed 12 patients of nocardiosis in EAS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nocardiosis most frequently presents with pulmonary disease, followed by disseminated disease, extra-pulmonary disease [such as in the central nervous system and primary skin and soft tissue disease (2)]. Nocardiosis is regarded as an opportunistic infection, with the majority of infections occurring in immunocompromised patients, including those with long-term corticosteroid exposure, malignancy, human immunodeficiency virus (HIV) infection, and history of transplantation (3)(4)(5)(6)(7), associated with high mortality of 34.5-40% (3,4). Xu L. et al (8) reviewed 12 patients of nocardiosis in EAS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of these cases, 44% had some CNS involvement, but CNS only involvement was only in 9% of cases [3]. Nocardia bacteremia is so extremely rare that in the last 20 years, only 227 cases have been reported in English language literature [4]. As there is a propensity for Nocardia to be attracted to the CNS, and if symptoms are suggestive of the presence of CNS disease or pulmonary nocardiosis is present, brain imaging is required to exclude CNS involvement in immunocompetent and immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is because symptoms of CNS nocardiosis are often nonspecific such as headache, seizures, focal neurologic deficits, fever and can even present without any signs of infection [2]. The diagnosis of CNS nocardiosis is more complicated due to blood cultures being positive in only 38% of cases despite the assumption that spread is hematogenous [4]. Therefore, it is crucial to consider CNS nocardiosis in patients with brain lesions, especially those who are immunocompromised such as patients with acquired immunodeficiency syndrome (AIDS), organ transplant recipients, those on immunosuppressive therapy, or those with other opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 312 isolates, 3 % were incorrectly classified by this method, including 3 strains of N. asteroides which were misidentified as N. neocaledoniensis [ 9 ]. Concerning Nocardia bacteremia, the last study of Williams et al reported more than 100 cases of invasive infections [ 10 ]. The most frequent species isolated were N. farcinica (33 %) followed by N. nova complex (10 %).…”
Section: Discussionmentioning
confidence: 99%